Gender in cross-cultural perspective - Bretel, Caroline B.; Sargent, Carolyn Fishel 1947- (Upper Saddle River, New Jersey Prentice Hall, 2001)
This anthology introduces readers to the most significant topics in the field of anthropology of gender--drawing from the most recent, diverse literature on gender roles and ideology around the world. A clear, accessible approach to the subject matter includes topics such as biology, gender, and human evolution; gender and prehistory; domestic and public worlds; the cultural construction of gender and personhood; culture and sexuality; division of labor; property and the state; household and kinship; ritual and religion; politics; reproduction; colonialism, development, and the global economy.
I. Biology, gender, and human evolution -- II. Gender and prehistory -- III. Domestic worlds and public worlds -- IV. The cultural construction of gender and personhood -- V. Culture and sexuality --VI. Equity and inequity: The sexual division of labor and gender stratification -- VII. Gender, property, and the state -- VIII. Gender, household, and kinship -- IX. Gender, ritual, and religion -- X. Gender, politics, and reproduction -- XI. Colonialism, development, and the global economy.
Includes bibliographical references.
Keywords: Sex role -- Cross-cultural studies